Analisis Pengaruh Citra Destinasi Dan Lokasi Terhadap Minat Berkunjung Kembali - Siti Fatimah (Sekolah Tinggi Maritim Yogyakarta, 2019)
This study aims to find out : 1.To find out the effect of the Destination Image and Location on the Interest to Revisit simultaneously, 2. To find out the influence of the Destination Image and Location on the Interest to Revisit partial, 3. To find out between the Destination Image and Loksai which most influence the Return Visit Interest. The population in this study is visitors or tourists who come to Ledok Sambi Eco Playground Kaliurang. Sampling technique by convenience sampling. Convenience sampling is a method of collecting data from respondents, which is based on the willingness to be respondents who can provide and are able to provide adequate information to researchers. And taken a sample of 100 respondents. Instrument test equipment uses SPSS for Windows 17.0 and to test hypotheses using multiple linear regression. The results of this study based on the results of the F test show the destination image and location simultaneously influence the interest in returning. Based on the results of the t test, the image of the destination has a significant positive effect on the interest in revisiting, while the location has a positive but not significant effect on the interest in returning. Destination image has the most dominant influence on Returning Interests.